BEKSAN GOLEK AYUN-AYUN GAYA YOGYAKARTA DALAM PERSPEKTIF AKSIOLOGI - Sri Widayanti (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2015)
The Golek Ayun-ayun dance of Yogyakarta's style is a sacred Golek dance style in Javanese tradition that has come down through generations as a national heritage. This dance is a classical Javanese dance comes from the court of Yogyakarta. It depicts a young woman's desire to always look her best.The Golek Ayun-ayun dance celebrates feminine beauty and appeal, including the coquettish dance because this dance portrays a woman who was dressed up. Many varieties of these dances that depict women being dressed up, like for example stole (sondher/sampur) games movement, or pairs of the ring (ali-ali), there is also look in the mirror (ngilo) and so forth. For Golek Ayun-ayun dance which the source comes from Ngayogyakarta court has standard rules or provisions, so it will not change the principle meaning.The principles of classical Javanese dance/Joged Mataram are Sawiji (concentration of mind), Greged (enthusiasm, consciousness), Sengguh (self-confidence), Ora Mingkuh (no surrender). Library research is done by collecting data and completed by interview. The material object of the research is Golek Ayun-ayun dance, and the formal object is axiology. Data analysis by descriptive, Verstehen, interpretation, hermeneutics, comparison, and heuristics method. The result showed that the elements used to organize the dancer makeup and fashion, also the beautiful movement of Golek Ayun-ayun dance is the content /meaning of makeup, fashion, and beautiful movement of Golek Ayun-ayun dance style, while the whole is external form. It contains the aesthetic value as an element of art or the art of dance. The art values in the movement, rhythm, makeup and fashion of Klana Raja dance are sensuous value, formal value, cognitive value, and life value.